PENGARUH DIMENSI KARIR TERHADAP KINERJA ORGANISASI DENGAN STRUKTUR ORGANISASI SEBAGAI MODERASI (Studi pada Manajer-Manajer Perusahaan di Jawa-Tengah) - Bambang Suko Priyono (Jurnal Bisnis dan Ekonomi, 2010)
This research examined the influence of career system dimentions on company performanceand organization structure as moderation variable. Career system dimentions consisting of; 1)career clarity & development, 2) promotion & reward system, and 3) job security. This researchtested to company managers in central Java. Five hundred questionnaires were distributed, 219questionnaires returned and 214 questionnaires were included in the analyses. Multipleregressions was used to examined the effect career system dimentions on performance. Next step,the researcher examined moderating effect of structure on the effects of career system onperformance. The result of multiple regressions indicated that career clarity & development,promotion & reward system have positive and significant effect on performance. In addition, therole of organization structure as moderating variable was supported.Keywords: organization performance, career clarity & development, promotion & reward system,job security and organization structure.